Menakar Kesyariahan Fintech Syariah di Indonesia - Aziz, Fathul Aminudin (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The development of information technology penetrated into all financial sectors, including sharia financial technology (Fintech). OJK as a regulator of the financial industry has issued regulations, to anticipate the development and utilization of IT in the financial industry such as lending, personal finance, crowdfunding, electronic money, investment investments, payment gateways, wealth management, and various other startups. Shari'ah literacy needs to be improved by giving an understanding that shari'ah is label and nature, theory, and practice, so halal is measured by how many elements of sharia are fulfilled. As for the elements of Islamic fintech in Indonesia, among others, accountability, transparency of information, fairness, equality, social piety, avoidance of transactions that are reckless, maysir, gharar, risywah, tadlis, israf, and halal. different amounts depending on how much the shari'a element is fulfilled. The greater the halal dose is fulfilled, the greater the halal, and vice versa the smaller the halal element is fulfilled, the smaller the halal value of its fintech transactions.